Strategic testing plan for ambulatory surgery centers after the COVID-19 pandemic. (4th June 2022) - Naidu, Ramana; Sheth, Samir; Chaturvedi, Rahul; Chakravarthy, Krishnan
Abstract: As the curve continues to flatten during the severe acute respiratory coronavirus 2 (SARS-CoV-2) pandemic, and more physicians resume outpatient clinical work, the question arises of how to ensure the safety of the patients and staff while performing cases. Many institutions and health-care offices have turned to screening questionnaires to determine the likelihood of coronavirus disease 2019 (COVID-19) positivity. However, screening questionnaires are woefully inadequate as studies have shown that roughly 6.4% to 50% of patients may spread this virus without any symptoms. In this study, we have outlined a proposal to restart elective procedures after the curve has flattened in a certain locale, particularly for ambulatory surgery centers (ASCs). Until additional data are collected for specific sensitivity and specificity values for PCR testing, we recommend performing 2 consecutive polymerase chain reaction (PCR) tests to minimize false negative rates. The algorithm described in this study can help ASCs begin their practices and provide local public health officials with valuable data that can help establish true sensitivity and specificity rates for these tests.